2013
DOI: 10.5665/sleep.2952
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Working Memory Performance in Primary Insomnia

Abstract: These data establish a profile of abnormal neural function in primary insomnia, reflected both in reduced engagement of task-appropriate brain regions and an inability to modulate task-irrelevant (i.e., default mode) brain areas during working memory performance. These data have implications for better understanding the neuropathophysiology of the well established, yet little understood, discrepancy between ubiquitous subjective cognitive complaints in primary insomnia and the rarely found objective deficits d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
124
3
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(137 citation statements)
references
References 37 publications
(42 reference statements)
8
124
3
2
Order By: Relevance
“…For example, the study of Cellini et al 13 shows that insomniacs have a worse performance in tests involving work memory. The study by Drummond et al 20 points out that insomniac patients show less activation of the frontoparietal system involved in working memory. In these patients, brain areas typically involved in tasks involving working memory would not be engaged in the operation; no activation was observed for any other brain area to compensate for non activation of this system.…”
Section: Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the study of Cellini et al 13 shows that insomniacs have a worse performance in tests involving work memory. The study by Drummond et al 20 points out that insomniac patients show less activation of the frontoparietal system involved in working memory. In these patients, brain areas typically involved in tasks involving working memory would not be engaged in the operation; no activation was observed for any other brain area to compensate for non activation of this system.…”
Section: Limitationsmentioning
confidence: 99%
“…No study indicated who administered the neuropsychological tests. Only six articles matched participants for age, [12][13][14]16,20,21 in contrast to the other four articles. 15,19,22,40 None of the studies indicated the level of education of the participants, even though it is a well known fact that these variables influence cognitive performance.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…An investigation of insomniac versus healthy controls on memory consolidation tasks, where recovery sleep was made available, identified the insomniacs as having substantially reduced memory consolidation [7]. Brain injury MRI studies reported reduced activation of task-related working memory regions in insomniac patients as compared to age matched controls [8]. The right dorsolateral prefrontal cortex reflected reduced modulation with increasing task difficulty.…”
Section: Introductionmentioning
confidence: 99%
“…Insomnia is common in the young adult population [1]. Neurobehavioral measures have substantiated the hyper arousability and reduced cognitive functioning behaviors [2,8]. The current study was designed as a case control study to measure cognitive functioning in a young adult presenting with insomnia.…”
Section: Introductionmentioning
confidence: 99%